Empowering Future Pharmacists in Chemistry Analysis of Nutraceuticals - Setiawan, Vendra; Risthanti, Reine Risa; Makayasa, Citra Hayu; Alkindi, Fawandi Fuad; Cahyani, Ayu Eprilita Fitri Ika; Makhnunah, Ninis (LP2M INSURI Ponorogo, 2024)
The community service aims to empower future pharmacists in East Java, Indonesia, by enhancing their understanding of nutraceuticals through chemistry analysis. Students gain essential skills for their academic pursuits through practical training in chromatography analysis and antioxidant activity measurements. The service equips students with practical skills in analyzing nutraceuticals, preparing them for further pharmacy studies. A training program was carried out for 88 SMA and SMK Farmasi students using Participatory Action Research (PAR). The main subjects covered were analysis using thin-layer chromatography, evaluation of functional groups in polyphenols, and assessment of antioxidant effectiveness. Pharmacy lecturers facilitated the program, guiding participants in practical competencies. The outcomes were successful, with a better understanding of nutraceuticals and valuable analytical skills gained. The significance of practical training and educational interventions in preparing students for advanced pharmacy studies is emphasized by this service.